2010
DOI: 10.1111/j.1467-7652.2010.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting specific genes for RNA interference is crucial to the development of strong resistance to Rice stripe virus

Abstract: SummaryRice stripe virus (RSV) has a serious negative effect on rice production in temperate regions of East Asia. Focusing on the putative importance of the selection of target sequences for RNA interference (RNAi), we analysed the effects of potential target sequences in each of the coding genes in the RSV genome, using transgenic rice plants that expressed a set of inverted-repeat (IR) constructs. The reactions of inoculated transgenic T 1 plants to RSV were divided subjectively into three classes, namely h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 54 publications
2
46
0
Order By: Relevance
“…While previous studies have reported the used of RSV CP and SP sequences in single transgene constructs (Ma et al, 2011;Shimizu et al, 2010), the RNAi effectiveness was quite different. For instance, RNAi transgenic rice plants harboring pSP-specific sequences did not exhibit enhanced RSV resistance (Shimizu at al., 2010).…”
Section: Rt-pcr Analysis Of Invading Viral Gene Expressionmentioning
confidence: 91%
See 2 more Smart Citations
“…While previous studies have reported the used of RSV CP and SP sequences in single transgene constructs (Ma et al, 2011;Shimizu et al, 2010), the RNAi effectiveness was quite different. For instance, RNAi transgenic rice plants harboring pSP-specific sequences did not exhibit enhanced RSV resistance (Shimizu at al., 2010).…”
Section: Rt-pcr Analysis Of Invading Viral Gene Expressionmentioning
confidence: 91%
“…For instance, not all RNAi constructs that target viral RNAs are equally effective in preventing RSV infection. Shimizu et al (2010) reported that nearly 90% of the dsRNAi-trigger p4 (SP) transgenic plants were susceptible to RSV infection. Upon considering these results, it is suggested that down-regulation of SP expression appears to be insufficient for the suppression of viral gene expression related to RSV proliferation.…”
Section: Rt-pcr Analysis Of Invading Viral Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of [85,86] stranded RNAs (dsRNAs), which are labeled as S1to S10, as they occur in the electrophoretic pattern of migration on polyacrylamide gels like SDS.…”
Section: Transgenic Mechanism As Silencing Suppressormentioning
confidence: 99%
“…In one study, eight different genes of PVY were targeted and the percentage of resistant plants obtained ranged from 33 % to 64 % (Chen et al 2010). Not all invert repeat constructs targeting different genes of the Rice stripe virus (RSV) were equally effective in preventing RSV infection (Shimizu et al 2011). It is essential to target the viral gene that plays an important role in viral proliferation.…”
Section: Virus-derived Hprna-mediated Resistancementioning
confidence: 99%